Newly enrolled teachers in 'Specialized Educational Support': Recorded voices in narrative letters (Revista Contexto & Educação, 2024)
This paper aims at understanding how teachers who recently joined Atendimento Educacional Especializado (AEE) experience this process and work to face the challenges into work field. The nature of research is qualitative and data was produced by narrative letters written by four new AEE teachers who are also participants in projeto de formação continuada Intercâmbio entre Salas de Recursos Multifuncionais, carried out by Distrito de Educação I – a body of municipal education network of Fortaleza, Ceará. The data were analyzed by Análise Textual Discursiva (ATD). Results show that joining AEE is influenced by several elements, such as: teacher's motivation towards Special-Needs Education; the anxieties, insecurities and dilemmas caused by the new demands from work field; and the contributions acquired by continuous professional development to overcome the challenges faced every day. Thus, professional induction programs are necessary. Brazilian education networks should be responsible for that so that new AEE teachers can be heard and supported in their work field.
Keywords: Atendimento Educacional Especializado; New teacher; Continuing training; Inclusion